2008
DOI: 10.1111/j.1365-2648.2008.04621.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the contribution of nursing in the community to the health of the people of Scotland: integrative literature review

Abstract: There is little research evaluating the impact of community nursing actions. Adequately resourced research is needed to strengthen the evidence base to support nurses in the community in delivering effective and efficient care that meet the health needs of people and communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 74 publications
(157 reference statements)
0
12
0
Order By: Relevance
“…A screening and appraisal tool for qualitative papers adapted from Noyes and Popay [35] and Kennedy et al [36] and a quality assessment tool adapted from the Effective Public Health Practice Project [37] for quantitative studies were used. The quality of evidence for quantitative and qualitative papers was appraised using the Scottish Intercollegiate Guidelines Network (SIGN) criteria [34].…”
Section: Methodsmentioning
confidence: 99%
“…A screening and appraisal tool for qualitative papers adapted from Noyes and Popay [35] and Kennedy et al [36] and a quality assessment tool adapted from the Effective Public Health Practice Project [37] for quantitative studies were used. The quality of evidence for quantitative and qualitative papers was appraised using the Scottish Intercollegiate Guidelines Network (SIGN) criteria [34].…”
Section: Methodsmentioning
confidence: 99%
“…The study reported here emerged as a development from an earlier integrated literature review commissioned by the Scottish Government on the contribution of community nursing to health outcomes. That review of international literature demonstrated, among other things, that little is known about how anticipatory care is understood and delivered by community nurses (CNs) (Kennedy et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A previous literature review (Kennedy et al. 2008) had identified a lack of studies in community nursing in relation to anticipatory care.…”
Section: Introductionmentioning
confidence: 99%
“…Roles and professional identities have been redefined in the community practice setting with a movement towards person centred care [16,33]. Expertise has been redistributed with the ‘up skilling’ of nurses leading to more complex patient cases being seen by the GP as s/he determines.…”
Section: Resultsmentioning
confidence: 99%